2019
DOI: 10.31083/j.jin.2019.01.12
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-362-3p attenuates motor deficit following spinal cord injury via targeting paired box gene 2

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Luciferase reporter assays were performed as previously reported. 28 When the cell confluence was at 70-80%, 1 μg luciferase reporter plasmid and miR-608/miR-NC were cotransfected into U-138MG or U-251MG cells. The protein was extracted 24 hours after transfection.…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…Luciferase reporter assays were performed as previously reported. 28 When the cell confluence was at 70-80%, 1 μg luciferase reporter plasmid and miR-608/miR-NC were cotransfected into U-138MG or U-251MG cells. The protein was extracted 24 hours after transfection.…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…Peripheral nerve injury often leads to refractory neuropathic pain [2,29]. Studies using animal model have demonstrated that neuropathic pain induced by peripheral nerve injury is often accompanied by apoptosis of spinal DRG neurons [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain refers to the douleur anormale (abnormal pain), caused by damage and dysfunction of the central or peripheral nervous system [1,2]. Neuropathic pain is one type of chronic pain, whose main clinical manifestations include hyperalgesia, paresthesia, ambulatory pain and allodynia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belonging to a class of small non-coding RNA containing 18–25 nucleotides, which completely or partially bind the sequence of target genes, inhibit protein translation by post-transcription regulation [ 15 , 16 ]. Multiple target genes can be regulated by one single miRNA, while different miRNAs are able to affect the same gene to control protein suppression.…”
Section: Introductionmentioning
confidence: 99%